2009
DOI: 10.1063/1.3062742
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved spectroscopy on GaN nanocolumns grown by plasma assisted molecular beam epitaxy on Si substrates

Abstract: A detailed study of excitons in unstrained GaN nanocolumns grown by plasma assisted molecular beam epitaxy on silicon substrates is presented. The time-integrated and time-resolved photoluminescence spectra do not depend significantly on the ͑111͒ or ͑001͒ Si surface used. However, an unusually high relative intensity of the two-electron satellite peak of the dominant donor-bound exciton line is systematically observed. We correlate this observation with the nanocolumn morphology determined by scanning electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
86
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 39 publications
17
86
3
Order By: Relevance
“…However, it must be kept in mind that other effects can influence the transition intensity and energies. Among them, the possibility of local potential variations due to the distribution of impurities 14 or the coupling between neighboring ZB inclusions, which explains the presence of peaks with intermediate energies. Indeed, for narrow ZB inclusions the confined electron wave function strongly extends into the WZ barriers, as can be also seen in Fig.…”
Section: à3mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it must be kept in mind that other effects can influence the transition intensity and energies. Among them, the possibility of local potential variations due to the distribution of impurities 14 or the coupling between neighboring ZB inclusions, which explains the presence of peaks with intermediate energies. Indeed, for narrow ZB inclusions the confined electron wave function strongly extends into the WZ barriers, as can be also seen in Fig.…”
Section: à3mentioning
confidence: 99%
“…12-14) have been studied in the bulk material. Both theoretical 15,16 and experimental 11,14 studies have shown that the band alignment between the WZ and ZB phases in nitrides is type-II. Basal SFs can be regarded as a single cubic sequence of planes (ABC) in the hexagonal matrix (ABAB…) and are associated with a strong luminescence signal due to bound excitons at energy 3.41-3.42 eV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of the latter was also demonstrated in GaN NWs [23], simultaneously with dramatic ageing effects (radical changes in micro-PL spectra, after long exposure to ambient air) resulting from surface alteration. Surface excitons in GaN NWs and NCs (observed at low temperatures, thus in vacuum) were proved to involve donors randomly distributed at variable distance from the surface [23,24]. For completeness, let us mention that surface modifications of transport properties in devices embedding disordered nitride or ZnO NWs, when exposed to certain gases, led to new concepts of gas sensors [25].…”
Section: Introductionmentioning
confidence: 99%
“…The rst one was a relatively narrow peak at 3.45 eV that had a lifetime of about 0.6 ns (longer than DX lifetime = 0.4 ns). This peak was reported in literature as characteristic for GaN nanowires [1] and related to excitons bound to surface defects (SDX) [2] or two-electron recombination of the DX near the surface [5]. The nanowires have a large area of side walls that are non-polar (1100) planes and probably can bind excitons.…”
Section: Resultsmentioning
confidence: 99%